VARIABILITY ANALYSIS OF CHLOROPHYLL-A DISTRIBUTION ON THE COAST OF SOUTHWEST ACEH USING AQUA MODIS IMAGE - Suriani, Mai; Rahmi, Mira Mauliza; Kusumawati, Ika; Islama, Dini; Dewinta, Astrid Fauzia; Heriansyah, Heriansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Chlorophyll-a has an important role in determining the trophic status and estimation of the fertility level of waters. The aim of this study was to analyze the variability of the concentration of chlorophyll-a on the coast of Southwest Aceh. This study uses remote sensing technology using Aqua MODIS imagery, the image used is an annual Level 3 Standard Mapped Image (SMI) chlorophyll-a image with a period of 7 years from 2015 to 2021 and has a spatial resolution of 4 km. The image is processed using software, namely SeaDAS and ArcMap. The results of this study showed that the distribution of the highest annual chlorophyll-a concentration was in 2019 at 0.29 – 2.27 mg/m3, and the lowest chlorophyll-a concentration was found in 2020 ranging from 0.29 – 1.02 mg/m3. The average concentration of chlorophyll-a in Southwest Aceh waters for 7 years (2015-2021) shows a low chlorophyll-a concentration ranging from 0.29 to 1.22 mg/m3 and belongs to oligotrophic and mesotrophic waters.